TESTING OF THE EVALUATION METHODOLOGY FOR SHIP’S PLANNED MAINTENANCE SYSTEM DATABASE - Stazić, Ladislav; Stanivuk, Tatjana; Mihanović, Vice (Journal of Applied Engineering Science, 2019)
Ship’s Planned Maintenance Systems are in use for a long period of time, but database quality, configuration and content are still not standardized. Factors affecting the database quality, configuration and content are quality of raw data, experience and knowledge of database creation team, importance given to computerized PMS and care assigned to evaluation of finished product. Evaluation of finished product, i.e. ship’s Planned Maintenance System Database is an action requiring specified knowledge and qualifications, as well as experience in performing the task. Even when evaluators fulfill all needed requirements, credibility of the obtained results is questionable due to their subjectivity. One of the tools to decrease that problem is the Evaluation Methodology for Ship’s Planned Maintenance System Database has been developed. A research, described in the paper, has been performed to test that aspect of the Methodology. Three Ships Planned Maintenance System Databases were evaluated by four different evaluators, first using only their experience, than using the Methodology. Results of the research are presented in the paper together with comparison of findings. All presented points that usage of the Methodology is a necessity during evaluations of ship’s Planned Maintenance System Databases.
Keywords: database; planned maintenance; questionnaire; quality evaluation; evaluation methodology; planning